Nilai Hematologi, Denyut Jantung, Frekuensi Respirasi, dan Suhu Tubuh Ternak Sapi Perah Laktasi di Pangalengan - Agik Suprayogi; Ganjar Alaydrussani; Asep Yayan Ruhyana (Institut Pertanian Bogor, 2017)
Pangalengan is located in the high land region with an altitude of 1.000-1.420 m above sea level, which has an average temperature of 17.80 ± 1.46 0C and humidity of 63.99 ± 2.74%. These environmental conditions will affect the physiological values of dairy cattle, especially during the lactation period. However, information about the physiological parameters of lactating cows in this area is not available. This study used 20 lactating dairy cows, and physiological values were measured in the morning, midday, and afternoon. The ranges of heart rate, respiration rate, and rectal temperature of dairy cows during lactation period were 59.82-72.02 times/min, 26.01-36.69 times/min, and 37.32-38.36 0C, respectively. The range of hemoglobin, hematocrit, erythrocytes, and leukocytes of lactating dairy cows was 8.29-9.51 g/dl, 24.52-29.70%, 6.10-8.18 million/µl, and 6.220-10.600 cells/µl, respectively. The range of differential leukocyte of lactating dairy cows were lymphocyte 32.64-63.14%, neutrophils 28.34-53.24%, monocytes 0.41-4.85%, eosinophils 1.58-15.78%, and basophils 0%, respectively. The range of a ratio of N/L of lactating dairy cows was 0.41-1.63. This study concludes that lactating dairy cows maintained under mild Pangalengan climatic conditions still show physiological values within the normal range